The Influence of Knee Extensor and Ankle Plantar Flexor Strength on Single-Leg Standing Balance in Older Women - Weerasak Tapanya; Sinthuporn Maharan; Patchareeya Amput; Noppharath Sangkarit; Boonsita Suwannakul (Journal of Functional Morphology and Kinesiology, 2023)
Impaired balance is a significant risk factor for falls among older adults. The precise impact of lower-extremity muscles, including the proportion of muscle strength, on the performance of single-leg standing balance tests in older individuals is very interesting. The aim of this study is to examine the correlation between the knee extensor (KE), ankle plantar flexor (AP) muscle strength, and performance in single-leg standing balance tests in older females. Additionally, it aims to evaluate the combined proportion of KE and AP muscle strength in maintaining balance during single-leg standing. A total of 90 older females (mean age 67.83 ± 8.00 years) were recruited. All participants underwent maximum voluntary isometric contraction (MVIC) testing of the KE and AP muscles, as well as single-leg standing balance tests with eyes open (SSEO) and eyes closed (SSEC). To examine the influence of KE and AP muscle strength on balance performance, multiple regression analysis was conducted. Low correlations were found between SSEO and MVIC of KE and AP muscles, but moderate correlations were found with percentage of MVIC to body weight ratio (%MVIC/BW). The best model for SSEO included 0.99 times of the %MVIC/BW of AP and 0.66 times that of KE muscles as independent predictor variables (r = 0.682). In conclusion, AP muscle strength was found to have a greater impact on single-leg standing balance compared with KE muscle strength.